A new species of Mycterothrips Trybom (Thysanoptera: Thripidae) from India with new record of the genus Paithrips Nonaka & Jangvitaya - Singha, Devkant; Patidar, Abhishek; Kumar, Vikas; Tyagi, Kaomud (Zootaxa, 2021)
Mycterothrips nainiae sp. n. (Thripinae) is described and illustrated from India, and one genus and species, Paithrips circularis Nonaka and Jangvitaya, is newly recorded from India. A key to species of Mycterothrips from India is also provided. The DNA barcode data using partial mitochondrial cytochrome c oxidase subunit I (mtCOI) from the holotype also five sequences of Paithrips circularis were generated.